An uncertainty budget for the precursor Watt balance for South Africa - Mametja, Thapelo Given (Department of Physics, 2020)
The 26th General Conference on Weights and Measures (CGPM) held on the 16th November 2018 has adopted the revision of the International system of units (SI) to be based on the fundamental physical constants.